ANALISIS KEAKTIFAN PENGELOLAAN HUTAN KEMASYARAKATAN DI AREAL HKM BANGKENG BUKIT DI DESA BONTONYELENG, KECAMATAN GANTARANG, KABUPATEN BULUKUMBA - Yusran Yusran; Muhammad Alif K Sahide; Adrayanti Sabar; Asfar Mirna (Universitas Muhammadiyah Malang, 2019)
Community forest is a forest management concept that is for poor citizens who live in and around a forest area and rely their lives on the use of forest resources, IUPHKm which is forest farmer groups of Bukit Indah in Bontonyeleng village, Gantarang district, Bulukumba regency. After running five years, the monitoring of the implementation of the Community forest General Plan document is necessary in terms of institutional and business management aspects. To assess whether community forest management is truly active management or hollow management, it is analyzed by comparing management planning and its implementation on production component, distribution, and institution aspects with obeservation method, interview and document analysis so that the management of HKm Bukit Bangkeng is categorized as active forest management due to the implementation of activity the dominant field that has been done.